2008
DOI: 10.1002/cssc.200700069
|View full text |Cite
|
Sign up to set email alerts
|

Regiodivergent Baeyer–Villiger Oxidation of Fused Ketones by Recombinant Whole‐Cell Biocatalysts

Abstract: Recombinant Escherichia coli cells expressing monooxygenases of different bacterial origin were evaluated in microbial Baeyer-Villiger oxidations of racemic fused ketones. During the enzymatic oxidation process, both the "normal" lactone generated by migration of the more-substituted carbon atom and/or the "abnormal" lactone resulting from migration of the less-substituted carbon atom can be formed. Depending on the nature of the Baeyer-Villiger monooxygenase, either a regiodivergent biooxygenation to both lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 77 publications
2
23
0
Order By: Relevance
“…Different structural motifs, like aliphatic, cyclic, and polycyclic have been transformed to the corresponding esters or lactones. Despite the use of aerial oxygen under ambient reaction conditions, BVMOs display a remarkably high regio-, chemo-, and stereoselectivity (Fink et al 2011;Mihovilovic et al 2008;Snajdrova et al 2006). One remarkable example for the use of BVMOs in industry is given by Codexis, which produced Esomeprazole by applying a CHMO variant (41 mutations, 104-fold increased stability and activity) in 99 % enantioselectivity (Bong et al, 2011).…”
Section: Recent Bvmo Applications Single Enzyme Transformationsmentioning
confidence: 96%
“…Different structural motifs, like aliphatic, cyclic, and polycyclic have been transformed to the corresponding esters or lactones. Despite the use of aerial oxygen under ambient reaction conditions, BVMOs display a remarkably high regio-, chemo-, and stereoselectivity (Fink et al 2011;Mihovilovic et al 2008;Snajdrova et al 2006). One remarkable example for the use of BVMOs in industry is given by Codexis, which produced Esomeprazole by applying a CHMO variant (41 mutations, 104-fold increased stability and activity) in 99 % enantioselectivity (Bong et al, 2011).…”
Section: Recent Bvmo Applications Single Enzyme Transformationsmentioning
confidence: 96%
“…The racemic cis -bicyclo[3.2.0]hept-2-en-6-one ( 34 ) is a well-known substrate for CHMO from Acinetobacter sp. NCIMB 9871 and for many other BVMOs (Alexander et al 2012; Alphand and Furstoss 1992; Ferroni et al 2014; Fink et al 2011; Mihovilovic et al 2005b, 2008; Rial et al 2008b). After 24 h, the BVMO Lepto oxidized this racemic substrate almost completely to equal amounts of normal and abnormal lactones (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NCIMB 9871, the ee of each regioisomeric lactone was poor (Table 4), The oxidation of the fused ketone 35 or 36 by BVMO Lepto preferentially gave abnormal lactones. These compounds ( 35 or 36 ) have been reported as substrates on approximately 10 Type I BVMOs, and in all cases except the BVMO5 from M. tuberculosis H37Rv (Snajdrova et al 2006), approximately equal amounts of regioisomeric lactones or normal lactones have been preferentially produced (Alphand and Furstoss 1992; Fink et al 2012; Mihovilovic et al 2005a, 2008; Rial et al 2008b). …”
Section: Discussionmentioning
confidence: 99%
“…These are regiodivergent procedures in which it is possible to obtain both regioisomeric lactones (the normal or proximal one and the abnormal or distal one) from the starting ketone. Several Baeyer-Villiger monooxygenases have been used, showing a similar clustering between cyclohexanone monooxygenase (CHMO) and [52] E. coli cells expressing cyclohexanone monooxygenase from Acinetobacter calcoaceticus NCIMB 9871 (CHMO Acineto ) are able to oxidize racemic ketone 39 into a 51:49 mixture of the normal lactone 40 and the abnormal one 41 with a global yield of 63%, both lactones being achieved with high optical purity (>95% ee). [51] Studies on this biooxidation have shown inhibitory substrate and product concentrations of 0.2-0.4 g • L -1 and 4.5-5 g • L -1 , respectively.…”
Section: Oxidation Of â-Substituted Cyclic Ketonesmentioning
confidence: 99%